The impact of family-firm structure and board composition on corporate transparency: Evidence based on segment disclosures in Malaysia - Wan Hussin, Wan Nordin (University of Illinois, 2009)
The aim of this study is to contribute to the growing literature on the quality of accounting disclosures by family firms by investigating whether the alignment (entrenchment) effect leads to high (low) corporate transparency. Unlike previous studies, this study also examines the relationship between board composition and corporate transparency by distinguishing between the two types of nonexecutive directors, namely independent and affiliated directors. Using the enhanced segment disclosures by Malaysian firms in 2001/2002 as a proxy of corporate transparency, the results indicate that family firms are more inclined to disclose all the required items for the primary basis of segment reporting, consistent with Ali, Chen, and Radhakrishnan (2007) and Wang (2006). The result also indicates that firms with higher proportion of affiliated directors are more likely to make greater segment disclosures. However, no evidence is found to support the contention that independent directors and institutional investors promote corporate transparency, consistent with previous Malaysian studies.